Correlation between Intraocular Pressure Fluctuation with Postural Change and Postoperative Intraocular Pressure in Relation to the Time Course after Trabeculectomy - Kazuyuki Hirooka; Kaori Tenkumo; Eri Nitta; Shino Sato (Journal of Ophthalmology)
Background. To investigate the correlation between intraocular pressure (IOP) fluctuation with postural change and IOP in relation to the time course after trabeculectomy. Methods. A total of 29 patients who had previously undergone primary trabeculectomy with mitomycin C were examined. IOP was obtained at 1, 2, 3, 6, and 12 months and then every 6 months postoperatively. Results. The postural IOP difference before surgery was 3.0±1.8 mmHg, which was reduced to 0.9±1.1 mmHg at 1 month, 1.0±1.0 mmHg at 2 months, 1.3±2.0 mmHg at 3 months, 1.3±1.4 mmHg at 6 months, 1.4±1.5 mmHg at 12 months, and 1.1±0.7 mmHg at 18 months after trabeculectomy (P<0.01 each visit). The filtering surgery failed in 7 out of 29 eyes. Postural IOP changes were less than 3 mmHg in those patients who did not require needle revision at every visit. However, in patients who did require needle revision, the increase in the posture-induced IOP was greater than 3 mmHg prior to the increase in the sitting position IOP. Conclusions. Assessment of postural IOP changes after trabeculectomy might be potentially useful for predicting IOP changes after trabeculectomy.